2014
DOI: 10.1590/0034-737x201461040004
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de carbamato de etila em cachaças de alambique e em aguardentes industriais

Abstract: Este trabalho teve como objetivo verificar a ocorrência de carbamato de etila, o grau alcoólico e a acidez volátil em cachaças e aguardentes de cana. As amostras foram obtidas de fabricantes de São Paulo, Minas Gerais, Rio de Janeiro, Espírito Santo e Ceará, de sistema de produção em destilador de cobre ou coluna de aço inoxidável, e de estabelecimentos registrados ou não. As análises de acidez volátil e de grau alcoólico foram realizadas conforme metodologia descrita pelo Ministério da Agricultura, Pecuária e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…It is noteworthy that, even though there was an increase in EC concentration during the storage period, the concentration of this contaminant was well below the maximum limit established by the MAPA (210 μg L À1 ). Several other studies have demonstrated that concentrations of EC above the maximum limit established by the legislation can be found in cachaça (5,8,(49)(50)(51)(52).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that, even though there was an increase in EC concentration during the storage period, the concentration of this contaminant was well below the maximum limit established by the MAPA (210 μg L À1 ). Several other studies have demonstrated that concentrations of EC above the maximum limit established by the legislation can be found in cachaça (5,8,(49)(50)(51)(52).…”
Section: Resultsmentioning
confidence: 99%
“…For some authors, the copper from the still can contribute to the formation of EC, because it is possible for this metal to act as a catalyst in the formation of this contaminant . Baffa Júnior et al demonstrated that correlations exist between the concentration of EC and the parameters involved in the distillation process, such as the composition of the distillation columns (copper or stainless steel), type of heating (direct or indirect), the cut of the fractions (head, heart, tail) and the reflux ratio during the process.…”
Section: Resultsmentioning
confidence: 99%
“…A infraestrutura de redução dos resíduos de cobre na produção da cachaça é formada por elementos materiais como o destilador constituído por chapas de metal feitas de cobre, o aquecimento do mesmo, a cachaça destilada e um filtro de resina de troca iônica (resina catiônica) ou de carvão ativado instalado nos tanques de armazenamento da cachaça recém destilada para reduzir significativamente a graduação desse resíduo na bebida. Na ausência desses filtros, o cobre dá ensejo a outro elemento material nocivo, fruto de seu efeito catalítico: a formação do carbamato de etila, um composto cancerígeno ainda presente em muitas bebidas (LIMA et al, 2009;LELIS et al, 2014).…”
Section: Tratamento Dos Resíduos De Cobreunclassified
“…The same authors observed that most of their samples did not match the limits required for this parameter. Lelis et al (2014) Esters are the compounds with the greatest sensory impact in a distilled beverage. They stand out in the formation of fruity aromas.…”
Section: Compliance With Legal Parametersmentioning
confidence: 99%